NANOCÁPSULAS CONTENDO ÁCIDO ALL-TRANS-RETINOICO: EFEITO ANTITUMORAL VIA DIFERENCIAÇÃO CELULAR E ATIVAÇÃO APOPTÓTICA INTRÍNSECA EM CÉLULAS DE LEUCEMIA PROMIELOCÍTICA AGUDA - Homrich, Shayenne Scheffer (2017)
The Acute Promyelocytic Leukemia (APL), firstly described in 1957, is the most malignant type of acute leukemia. Currently, the knowledge of its pathophysiological mechanism at molecular levels became possible the development of efficient therapies making APL the most curable leukemia type. In this sense, APL is also used as a model on cancer advances, being the molecular treatment performed with all trans-retinoic acid (ATRA) that presents high efficiency at its control. However, several patients develop differentiation syndrome, as a side effect of this drug. In these terms, compared to another drugs, the cytotoxic antineoplastic agents present particular problems, as poor specificity, high toxicity and resistance susceptibility. An alternative strategy to decrease the ATRA cytotoxicity is the incorporation of this drug in polymer nanocapsules with oily core. In this work nanocapsules with lipid core containing ATRA (NA) were evaluated as their potential to inhibit cellular grow, to induce apoptosis, to interfere the cell cycle, and at APL cellular differentiation using NB4 cell line. Results showed that NA was able to overcome the cellular resistance to AL treatment, decreasing cell viability, inducing apoptosis, through BAX/BCL-2 gene expression, cell cycle arresting at G1 phase and cellular differentiation under 1.5 and 2.0 μM. Additionally, theses systems can contribute to increase the efficacy and reduce the toxicity due to the potential accumulation of nanoparticles at the tumor region due to increased vascular permeability of tumor vases. The ATRA incorporation in lipid nanocarriers is a interesting alternative to make possible its intravenous administration. Moreover, these systems present potential to drug accumulation at tumor tissue through a passive targeting called effect of permeability and increased retention.